The road to Hong Kong - Panama, Frank; Crosby, Bing, 1903-1977.; Hope, Bob, 1903-2003; Collins, Joan, 1933-; Metro-Goldwyn-Mayer. (Santa Monica, CA : MGM, 2002)
Harry (Crosby) and Chester (Hope) travel to Tibet to search for a drug to restore Chester's memory. Once they find the cure, Chester's memory becomes so good that he accidentally memorizes a secret formula for space navigation. Soon the two meet up with a beautiful spy (Collins) and get slightly sidetracked ... to another planet!
Title from disc surface.
Videodisc release of the 1962 motion picture.
Original screenplay by Norman Panama & Melvin Frank ; songs by Sammy Cahn and Jimmy Van Heusen.
Starring Bing Crosby, Bob Hope, Joan Collins, Dorothy Lamour, Robert Morley.
Not rated.
DVD, Dolby digital, mono., widescreen 1.66:1 theatrical release format.
Keywords: Video recordings for the hearing impaired; Feature films; Comedy films; French language materials; Spanish language materials